Two-stroke engine repair & maintenance - Dempsey, Paul (New York : McGraw-Hill, 2010)
Packed with photographs, this is a step-by-step, how-to guide for troubleshooting, repairing, and maintaining two-stroke engines--the types that power tens of millions of lawn equipment machines and small generators. Weed trimmers, edgers, leaf blowers, hedge trimmers, and portable pumps all run on two-stroke engines.
Includes index.
Keywords: Two-stroke cycle engines -- Maintenance and repair